KARAKTERISTIK BANK DAN KONDISI MAKROEKONOMI TERHADAP PROFITABILITAS PERBANKAN INDONESIA - Dendy Mohammad Prabowo; Wijaya, Richy; Efi Riana Sari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This research investigate bank-specific factors and macroeconomic indicators affect the profitability of Indonesian banks listed on the Indonesia Stock Exchange during 2019–2023. Specifically, it evaluates the effects of Capital Adequacy Ratio (CAR), Asset Management, Bank Branches, Deposits, Non-Performing Loan (NPL), and Inflation on Return on Assets (ROA), identifying which variables significantly enhance or diminish bank profitability. A quantitative, causal-comparative research design is employed using panel data regression. The sample consists of 33 banks observed over five years (2019–2023), forming a balanced panel dataset. Bank-specific factors include CAR, Asset Management, Bank Branches, Deposits, and NPL, while Inflation represents the macroeconomic factor. The results reveal that CAR, Asset Management, Bank Branches, and NPL significantly affect bank profitability. Conversely, Deposits and Inflation have an insignificant relationship with ROA. Theoretically, these findings reinforce the relevance of resource-based and efficiency theories in explaining bank performance. Practically, they suggest that banks should prioritize capital strength, optimize asset utilization, and control credit risk, rather than relying solely on deposit growth, to sustain profitability. Regulators can also apply these insights to design supervisory policies that strengthen resilience and operational efficiency.